Domain of Euler Mean in the Space of Absolutely $p$-Summable Double Sequences with $0< p (Analysis in Theory and Applications, 2018)
In this study, as the domain of four dimensional Euler mean $E(r,s)$ of orders $r$, $s$ in the space $\mathcal{L}_p$ for $0
Keywords: Summability theory; double sequences; double series; alpha-; beta- and gamma-duals; matrix domain of 4-dimensional matrices; matrix transformations.